Endocrine and physiological regulation of neutral fat storage in Drosophila. - Lehmann, M. (Molecular and Cellular Endocrinology, 2018)
After having revolutionized our understanding of the mechanisms of animal development, Drosophila melanogaster has more recently emerged as an equally valid genetic model in the field of animal metabolism. An increasing number of studies have revealed that many signaling pathways that control metabolism in mammals, including pathways controlled by nutrients (insulin, TOR), steroid hormone, glucagon, and hedgehog, are functionally conserved between mammals and Drosophila. In fact, genetic screens and analyses in Drosophila have identified new players and filled in gaps in the signaling networks that control metabolism. This review focuses on data that show how these networks control the formation and breakdown of triacylglycerol energy stores in the fat tissue of Drosophila.